Nomenclature of the symptoms of head and neck cancer: a systematic scoping review - Bradley, Paula T.; Lee, Ying Ki; Albutt, Abigail; Hardman, John; Kellar, Ian; Odo, Chinasa; Randell, Rebecca; Rousseau, Nikki; Tikka, Theofano; Patterson, Joanne M.; Paleri, Vinidh (Frontiers in Oncology, 2024)
Same as previous